Studi Fenomenologi Bahasa Gaul Dan Implikasinya Terhadap Keterampilan Berbahasa Indonesia Siswa Kelas IV Sekolah Dasar - Dhea Sylvia Ekha Tom Saputri (proceedings.icesy, 2026)
This study aims to explore the phenomenon of slang usage and its implications for the Indonesian language skills of fourth-grade elementary school students. The method used is a qualitative approach with a phenomenological study design, through observation in the school environment with direct observation without intervention, and the results are analyzed using instruments that employ horizontal stages and meaning unit clustering to discover the essence of the experience. The participants in this study were fourth-grade students from SDN Banjarsari 5, followed by in-depth interviews with fourth-grade teachers. The results of this study indicate that fourth-grade students actively use slang both inside and outside the classroom. The use of slang words is in line with popular words, social media, and online-based games. The implication is that students have difficulty separating language codes when the context requires formal language. This phenomenon creates a significant dichotomy in language proficiency and requires pedagogical intervention to integrate awareness of language context from an early age.